ASSESSMENT OF THE PRINCIPLE OF CREDIBILITY WITH REGARD TO GRANTING REFUGEE STATUS - Gojaeva, Kizeitar (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
The number of asylum seekers and recipients of international protection in Georgia has been progressively rising each year, influenced by the unstable circumstances prevailing both globally and regionally. Asylum seekers are considered clients with special needs, as they may be traumatized or suffer from health problems; in most cases, they do not speak the language of the host country or are unfamiliar with its legal system, which leads to heightened dependency on lawyers and increases the need for qualified legal aid. International law requires all states to respect, protect, and fulfill the human rights of every individual within their territory or jurisdiction, including asylum seekers, without discrimination. This obligation can only be fulfilled through the guarantee of access to legal aid, which serves as a cornerstone for the effective realization of fundamental rights. The paper focuses on the asylum seeker's right to qualified legal aid to develop recommendations that will contribute to improving access to justice. The accessibility of legal aid for asylum seekers requires further examination in the context of increasing migration in Georgia, where the demand for legal aid is growing daily.